DESIGN OF DISASTER MITIGATION INFOGRAPHIC FOR ECOTOURISM IN KALITALANG, BALERANTE VILLAGE - Negara, Malik Wiranata; Prameswari, Nadia Sigi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Indonesia is a country with high ecotourism potential, supported by its natural wealth and cultural diversity. However, its geographical location in the Pacific Ring of Fire makes it highly vulnerable to geological disasters, particularly volcanic activity. This phenomenon demands the integration of tourism development with adaptive and sustainable disaster mitigation efforts. One area that represents a model of mitigation-based ecotourism is Kali Talang, located on the slopes of Mount Merapi, Klaten Regency. Despite being in a disaster-prone zone, this area continues to function as a tourist destination as well as an educational space that provides understanding of volcanic hazards and risk reduction efforts. This work aims to convey information about volcanic disaster mitigation through a visual approach based on infographics, as an effective medium of public communication. By raising issues of risk and preparedness within the context of managing natural tourism areas, this work is expected to strengthen collective awareness and encourage the development of more resilient and sustainability-oriented tourism practices.